The role of microRNAs as regulators of systemic inflammatory response in anticonvulsant-induced metabolic syndrome - N. A. Shnayder; N. A. Pekarets; N. I. Pekarets; Yu. N. Bykov; V. V. Grechkina; D. V. Dmitrenko; M. M. Petrova; R. F. Nasyrova (Эпилепсия и пароксизмальные состояния)
Background. Metabolic syndrome induced by antiepileptic drugs (AED-MetS) is a serious adverse reaction (AR) that reduces the quality of life of patients with epilepsy and increases the risk of comorbid cardiovascular disorders affecting life expectancy. The risk of developing AED-MetS varies depending on various factors that account for a search for sensitive and specific biomarkers to predict its development, prevention, diagnosis and correction as well as related main domains (hypertension, dyslipidemia, central obesity, type 2 diabetes mellitus). Systemic inflammatory response and oxidative stress are important arms in both epileptogenesis and neurodegeneration, as well as AED-MetS pathogenesis.Objective: Systematization of the results from preclinical and clinical studies on the role of circulating blood microRNAs in the development and adverse course of the systemic inflammatory response as one of AED-MetS main domains in patients with epilepsy.Material and methods. The analysis of the results of fundamental and clinical studies on circulating microRNAs as epigenetic biomarkers of systemic inflammatory reactions in the mechanism of MetS and AED-MetS pathogenesis, which were included in the databases Google Scholar, PubMed/MEDLINE, MDPI, Scopus, and eLibrary, was carried out over the last decade (2014– 2024).Results. A systematic review has demonstrated that microRNAs can act as promising epigenetic biomarkers of AED-MetS, however, the role for different microRNAs and their paralogs on the development of this AR varies. As part of the current study, a microRNA signature was proposed depending on the risk and severity of the systemic inflammatory response and associated oxidative stress (the leading mechanisms of AED-MetS pathogenesis). The proposed signature consists of three groups of microRNAs, depending on their role in regulating the systemic inflammatory response: low, medium, and high risk.Conclusion. The role of microRNAs in regulating the systemic inflammatory response in AED-MetS requires to be further investigated and results of basic research translated into real-world clinical practice, since the studied microRNAs can not only trigger and exacerbate AED-MetS, but also initiate or support the neurodegenerative processes underlying epileptogenesis.